Marginal Zinc Deficiency and Environmentally Relevant Concentrations of Arsenic Elicit Combined Effects on the Gut Microbiome - Christopher A. Gaulke (American Society for Microbiology, 2018)
ABSTRACT Extensive research shows that dietary variation and toxicant exposure impact the gut microbiome, yielding effects on host physiology. However, prior work has mostly considered such exposure-microbiome interactions through the lens of single-factor exposures. In practice, humans exposed to toxicants vary in their dietary nutritional status, and this variation may impact subsequent exposure of the gut microbiome. For example, chronic arsenic exposure affects 200 million people globally and is often comorbid with zinc deficiency. Zinc deficiency can enhance arsenic toxicity, but it remains unknown how zinc status impacts the gut microbiome’s response to arsenic exposure and whether this response links to host toxicity. Using 16S amplicon sequencing, we examined the combinatorial effects of exposure to environmentally relevant concentrations of arsenic on the composition of the microbiome in C57BL/6 mice fed diets varying in zinc concentration. Arsenic exposure and marginal zinc deficiency independently altered microbiome diversity. When combined, their effects on microbiome community structure were amplified. Generalized linear models identified microbial taxa whose relative abundance in the gut was perturbed by zinc deficiency, arsenic, or their interaction. Further, we correlated taxonomic abundances with host DNA damage, adiponectin expression, and plasma zinc concentration to identify taxa that may mediate host physiological responses to arsenic exposure or zinc deficiency. Arsenic exposure and zinc restriction also result in increased DNA damage and decreased plasma zinc. These physiological changes are associated with the relative abundance of several gut taxa. These data indicate that marginal zinc deficiency sensitizes the microbiome to arsenic exposure and that the microbiome associates with some toxicological effects of arsenic. IMPORTANCE Xenobiotic compounds, such as arsenic, have the potential to alter the composition and functioning of the gut microbiome. The gut microbiome may also interact with these compounds to mediate their impact on the host. However, little is known about how dietary variation may reshape how the microbiome responds to xenobiotic exposures or how these modified responses may in turn impact host physiology. Here, we investigated the combinatorial effects of marginal zinc deficiency and physiologically relevant concentrations of arsenic on the microbiome. Both zinc deficiency and arsenic exposure were individually associated with altered microbial diversity and when combined elicited synergistic effects. Microbial abundance also covaried with host physiological changes, indicating that the microbiome may contribute to or be influenced by these pathologies. Collectively, this work demonstrates that dietary zinc intake influences the sensitivity of the microbiome to subsequent arsenic exposure.